Notes on the eradication of polio in Peru - Lossio, Jorge (2010)
This article examines the process of the polio eradication campaign in Peru (1985-1991) a polio initiative in Peru (1985-1991) an initiative of the Pan American Health Organization (PAHO) that was financed by the Rotary International. Therefore, this work shows the difficulties that the campaign had due to the lack of a good state apparatus as a result of the political, social and economic crisis of the 1980s and the situation of the internal armed conflict. Despite these difficulties, the team in charge of the eradication (doctors, nurses, Rotarians and members of civil society) carried out their work in both the "sweep" (mass vaccination) in both urban and rural areas. In addition, despite the lack of logistics, it was possible to carry out the epidemiological follow-up that ended in 1991 when the last case was found.